Markets, income and policy in a unified macroeconomic framework - Hongfei Sun (Queen's University, Department of Economics, 2011)
I construct a unified macroeconomic framework by incorporating frictional markets in a neoclassical environment. This framework is analytically tractable despite search frictions, income risks and endogenous money distributions. I use this framework to formalize a theory that the variety and the functioning of markets reflect the status of national income. In the model, households and firms have free access to goods markets with and without trading frictions, where the frictional markets are featured by competitive search. I characterize and prove the existence of a steady state. In equilibrium, the frictionless markets are generically used to smooth consumption, whereas the frictional markets are used only when households have sufficiently high expected real income. Uninsurable idiosyncratic income risks cause households to endogenously sort into various submarkets upon entry to a frictional market. Consequently, income inequality determines the dispersion of equilibrium trading protocols across frictional submarkets. In additional to the redistributive effects, both monetary and fiscal policies have their distinctive impacts on the intensive and extensive margins of frictional trading. The optimal policy program consists of money growth, proportional income taxes and proportional sales subsidies.
Keywords: E0; E4; E5; E6; H2; H3; 330; Market; Friction; Distribution; Competitive Search; Policy; Makroökonomik; Marktmechanismus; Einkommen; Risiko; Einkommensverteilung; Theorie